Assessment of Thermal Potential in Disc Brake of Transportation Unit - Javadov, M.Y.; Dolishniy, B.V.; Skrypnyk, V.S.; Zhuravlev, D.Y.; Nasirova, M.M.; Volchenko, N.A.; Malyk, L.B. (Herald of Azerbaijan Engineering Academy, 2021)
Potentials and their gradients are analyzed in mechanical, heat, chemical, electrical, magnetic fields arising during elektrothermomechanical interaction of friction pairs of disc-block tormos of vehicles. Influence of diffusion and adsorption potentials on formation of double electric layers on friction belts of solid disks during braking is shown. The effect of local thermal potential on the friction layer of the solid brake disc is considered from the point of view of obtaining excessive entropy. Stable state of elementary volume of disk friction belt layer is estimated through local functionals, which take into account fluctuation of its energy load.